Missing Link : Volatility and the Debt Intolerance Paradox - Catao, Luis (IMF Working Papers; Working Paper ;, 2004)
A striking feature of sovereign lending is that many countries with moderate debt-to-income ratios systematically face higher spreads and more stringent borrowing constraints than others with far higher debt ratios. Earlier research has rationalized the phenomenon in terms of sovereign reputation and countries' distinct credit histories. This paper provides theoretical and empirical evidence to show that differences in underlying macroeconomic volatility are key. While volatility increases the need for international borrowing to help smooth domestic consumption, the ability to borrow is constrained by the higher default risk that volatility engenders.